Modern Breastfeeding Options for Preterm Children in Neonatal Hospital - Irina A. Belyaeva; Leyla S. Namazova-Baranova; Elena P. Bombardirova; Tatiana V. Turti; Evgeniia A. Prikhodko ("Paediatrician" Publishers LLC, 2022)
The literature overview on the issue of breastfeeding in neonatal departments, including neonatal intensive care units, is presented. The importance of breastfeeding for newborns with perinatal pathology is justified, as breast milk is vital for these children due to its unique sanogenetic properties. Data on special preventive and therapeutic role of breastfeeding for premature infants is presented. Reasons that complicate the use of breast milk in neonatal hospitals were analyzed (including those related to insufficient bacteriological and virological safety of native breast milk due to methodological errors during its collection and usage). Particular attention was paid to ensuring the breastfeeding safety during new coronavirus infection pandemic. This difficult period has demonstrated and confirmed the expediency of combining two breastfeeding approaches in perinatal centers: use of maternal milk and use of donor breast milk. Another section of review is devoted to modern breast milk processing technologies. Use of electric clinical breast pumps is crucial for promoting and supporting breastfeeding in the perinatal center.